Peningkatan Performa dan Kualitas Daging Sapi Bali yang Diberi Imbuhan Tepung Jagung Dalam Ransum (MAIZE FLOUR SUPPLEMENTATION IMPROVE PERFORMANCE AND MEAT QUALITY OF BALI CATTLE) - Suryani, Ni Nyoman; Suarna, I Wayan; Mahardika, I Gede; Sarini, Ni Putu (Jurnal Veteriner, 2020)
Research has been conducted to evaluate the effect of corn flour supplementation in ration on the performance and quality of Bali beef. The study used 12 head of Bali cattle weighing 209362 kg. The experiment used a randomized block design with four treatments and and each group consisted of three replications. The four treatments are: Treatment A: Cattle given king grass feed and concentrate, Treatment B: Cows given king grass feed, concentrate and 1 kg of corn flour, Treatment C: Cows given king grass feed, concentrate and 1.5 kg corn flour and Treatment D: Cows given king grass feed, concentrate and 2 kg of corn flour. The concentrate used is commercial concentrate. Variables observed included: weight gain, feed consumption, Feed Conversion Ratio (FCR), carcass composition and quality, and meat quality. Every two weeks Bali cattle were weighed to see the weight gain. The results showed that supplementation of corn flour in the Bali cattle ration significantly (P <0.05) increase the consumption of dry matter, protein, energy and slaughter weight, and the highest was shown in treatment D respectively 7.66 kg/day; 966 g/day; 24,614 kcal/day and 389 kg.  Significant increase (P <0.05) and highest also occurred in treatment D of meat fat content that is 9.66% and carbohydrate meat of 24.614%.  Based on the results of this study, it can be concluded, supplementation of 1-2 kg corn flour in the Bali cattle ration can increase the growth and chemical quality of Bali beef, but it does not affect the percentage of carcass, pH, water holding capacity and cooking loss.